Územní ochrana přírody a soustava NATURA 2000 - Bůžková, Renáta (Univerzita Karlova, Právnická fakulta, 2015)
The thesis is focused on the theme, which is current almost every time, even in every state, and that is the protection of the nature. We all are a part of the nature, which is all around us. It must be protected, so as future generations can experience its beauty. The interest in the theme results from the author's job that is why the author decided to discuss the theme and outline its difficulties. The work itself is divided into three parts. Most of the first part focuses on the specific territorial nature and landscape protection, which consist in announcing various categories of specially protected areas; it also focuses on the providing tools for their protection and care. In the thesis, general territorial nature and landscape protection are not omitted, because they, using certain institutes, provide significant protection to the fragments of nature or territories, which do not attain such values to be declared as protected. In the second part of the thesis, the author discusses the type of territorial protection, which is relatively new in the Czech Republic and which was created in connection with accession to the EU. On the basis of the habitats directive and the birds directive, there a protection provided to the important European species of plants and animals, including birds, and for. Rigorózní práce je zaměřena na téma aktuální snad v každé době a i v každém státě, a to na územní ochranu přírody. My sami jsme součástí přírody a příroda je všude kolem nás. Je nutné ji chránit, aby i budoucí generace mohly poznat krásy nejen naší vlasti. Větší zájem o toto téma vzbudilo v autorce její zaměstnání, proto se rozhodla o něm pojednat a nastínit i jeho určitá úskalí. Práce samotná je rozdělena do tří částí. Většina první části je zaměřena na zvláštní územní ochranu přírody a krajiny spočívající ve vyhlašování jednotlivých kategorií zvláště chráněných území a na nástroje zabezpečující jejich ochranu a péči o ně. Opomenuta není ani obecná územní ochrana přírody a krajiny, která za použití určitých ...